Obesity-Induced Upregulation of ZBTB7A Promotes Lipid Accumulation through SREBP1. (9th January 2020) - Zhou, Jing-ping; Ren, Yan-dan; Xu, Qin-yu; Song, Yang; Zhou, Fei; Chen, Mei-Ya; Liu, Jing-jing; Chen, Li-Gang; Pan, Jin-Shui
Abstract : Objective . Nonalcoholic fatty liver disease (NAFLD) is among the most common chronic liver diseases. However, the pathogenesis of NAFLD is not still unclear. This study aims at evaluating the role of zinc finger and BTB domain-containing 7A (ZBTB7A) in NAFLD. Methods . Western blotting, real-time reverse transcription PCR (RT-PCR), and immunohistochemistry were submitted to evaluate the level of ZBTB7A in the high fatty diet- (HFD-) induced NAFLD mouse model. In vitro, the expression of ZBTB7A was assessed in oleic acid- (OA-) induced HepG2 cells with western blotting and RT-PCR. The luciferase reporter assay was used to estimate the effect of ZBTB7A on the SREBP1 and NF- κ B, and the ChIP assay was subjected to evaluate the direct binding to the SREBP1 promoter. Oil Red staining was used to detect lipid accumulation, and the ELISA was used to verify the levels of TG, T-CHO, and MDA. ZBTB7A was knocked down with siRNA, and RT-PCR was performed to analyze the lipogenesis-, fatty acid transporter-, and oxidation metabolism-related genes expression. The levels of ZBTB7A in primary hepatocyte, Kupffer, and hepatic stellate cells (HSCs) were tested by RT-PCR. Results . The upregulation of ZBTB7A expression was assessed in NAFLD mice, and ZBTB7A expression was positively correlated with TNF α, IL-6, TG, T-CHO, and MDA. ZBTB7A was highly expressed in the hepatocytes. In vitro, OA-induced ZBTB7A expression and ZBTB7A expression were closely associated with SREBP1c. ZBTB7A could activate the promoter activity of SREBP1 and activate NF- κ B activity. Interestingly, the direct binding of ZBTB7A in the SREBP1 promoter was acquired in HepG2 cells. Inhibition of ZBTB7A expression could attenuate OA-induced lipid accumulation, inhibit the expression of the lipogenesis-related genes and fatty acid transporter genes, and promote the expression of oxidation metabolism-related genes. Conclusion . ZBTB7A plays a significant role in the development process of NAFLD, and obesity-induced upregulation of ZBTB7A promotes lipid accumulation through activation of SREBP1 and NF- κ B. ZBTB7A may be a potential novel target for the therapy of NAFLD.